Asymptotic Behavior of Fractional Derivatives of Bounded Analytic Functions - Chyzhykov, I.; Kosaniak, Yu. (Журнал математической физики, анализа, геометрии, 2017)
We find sharp sufficient conditions for the boundedness of fractional derivatives of a bounded analytic function in a Stolz angle. If F ≠ 0 in the unit disc, the necessary and sufficient conditions for the boundedness of fractional derivatives of its argument in a Stolz angle are established.